Recent Advancements about the Respective Roles of Central and Intraorgan Nervous Systems in Regulation of the Gastrointestinal Tract Physiology and Morphology - Coulic, V. `; Prez, C. De; Iesuitova, N.; Makarova, L. F.; Maksimenkova, A.; Mikhalski, D. V.; Delrée, P. J. (Highlights on Medicine and Medical Research Vol. 4, 2021)
The role played by central nervous system in the general regulation and coordination of organ, tissue and even cell activities does not stop to excite the curiosity of investigators. Recently important data were obtained in the field of new neurotransmitters and other active molecules which mechanisms of actions and interactions were clarified. But the function of intra organ, local nervous system, its relations with the main brain and medullar centers remain a little enigmatic though much is known about tiny paths of afferent, efferent and inter neuronal transmission. In order to isolate the influence of central and intramural nervous system of the intestine, several situations were considered: 1) surgical interruption of nervous reflex links (NRI), which is always present in organ transplantation and often occurs in spinal cord trauma, 2) injury of the intramural nervous system with perfectly conserved links with central nervous system, for instance after intestinal ischemia and in Hirschprung disease. As control a technique of surgical directed re innervation (SDR) of the intestinal graft by suture of the divided mesenteric plexus was elaborated. A model of ontogenetic reconstruction of adult-like organs after syngeneic implantation into an adult organism of a fetal organ containing (intestine) or not (liver, pancreas) an organized intramural nervous system, was also used. The experiences on 101 dogs, 274 rats and 25 mice were conducted by the same team according to the rules of Bioethics. Performed investigations concerned testing nervous connection with central nervous system (Recto-enteric reflex presence, normal reaction to anticholinergic substance), evaluation of motility, secretion, membrane digestion of the intestine, as well as optic and electron microscopy of the target organs The results may be summarized as following. Disconnection from the CNS does not significantly affect more than a few days (influence of operation trauma) the intrinsic functions and the morphology of the intestine but has an incidence on the own rhythm of the organ activity which becomes “autonomous” and stops to be integrated into the whole regulation of digestive tract function. It creates such disorders as accelerated nutrient transit, hyper secretion, body weight loss. The activity of the remaining linked with central nervous system stomach and colon is modified in such a way that final digestive process is adapted and correctly realized (central nervous coordinating intervention). Restoration of central nervous reflex control of the operated intestine leads to the normalization of its activity and of the whole digestive process. The destruction of intramural nervous system either by prolonged ischemia, or by congenital dysplasia affects both function and morphology of the intestine. The ontogenetic complete development of a grafted fetal organ is possible only when it presents an intramural nervous system (for instance, intestine). If intra organ neurons are not organized as plexus, the graft development is partial and not coordinated: only isolated weakly organized structures develop (for instance in the ectopically grown fetal liver - bile ducts, hepatocytes column, in pancreas - endocrine cells isolated or in clusters), without any links between each other. So, if in reconstructive surgery of limbs of face, somatic nerve sutures are a routine procedure, on the other hand surgical or directed reconstruction of nervous links is practically unknown in solid organ grafting. Suturing vegetative nervous plexus surrounding large vessel irrigating the graft is technically simple and seems justified but probably still deserves further investigations for benefit confirmation. These findings may be interesting for the development of organ transplantation, when it may be useful to restore not only the vascular connections of the graft with the host, but also the nervous links of the transplant with the recipient central nervous system (brain and spinal medulla). This conception may be worthwhile in the treatment of such pathology as digestive difficulties in tetra and paraplegia patients on one side, of Hirschprung disease on the other side. It may also help to consider and understand the problems which may be either the consequences of central nervous system alterations for digestion or, on the contrary, the incidence of severe peripheral disorders for the brain activity.